Modified starch based on graft copolymerization, preparation method and application in PBAT
Through modified starch technology based on graft copolymerization, the high cost, low modulus and poor crystallization performance problems that PBAT exist in application are solved, and the mechanical and thermal properties of composite materials are significantly improved.
Patent Information
- Application Number
- CN202510059689.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Traditional non-degradable plastics cause pollution to the environment. PBAT, a biodegradable material, has high cost, low modulus and poor crystallization properties in applications. The starch is poorly compatible with PBAT, making it difficult to improve the mechanical and thermal properties of composite materials.
Through modified starch based on graft copolymerization, butenoyl chloride, triaminobenzyl alcohol and triethylamine are used as monomers to graft with starch, and amide and ester functional groups are introduced to reduce the hydrogen bonding between starch molecules, thereby improving plasticity and processability, and blending it with urea and glycerol composite plasticizers to enhance the mechanical and thermal properties of starch.
It significantly improves the strength, toughness and compatibility with PBAT, and improves the processing, mechanical and thermal properties of composite materials.
Smart Images

Figure CN119505095B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material modification, and in particular to modified starch based on graft copolymerization, a preparation method and application in PBAT. Background Art
[0002] The extensive use of traditional non-degradable plastics has caused serious pollution to the environment. With the enhancement of people's environmental awareness, biodegradable plastics have received widespread attention. Polybutylene adipate / terephthalate (PBAT) is one of the best commercially available fully biodegradable materials. It has good thermoplasticity, thermal stability, and ductility, and is widely used in disposable packaging and agricultural mulch films. Although PBAT has been commercialized, its high cost, low modulus, and poor crystallization performance limit the promotion and use of PBAT films. Starch is a natural polymer material with the advantages of low cost, renewability, and non-toxicity. Filling PBAT with starch is an effective way to reduce the cost of PBAT and improve its mechanical properties. However, the starch molecular structure contains a large number of hydroxyl groups, which have a large polarity and are difficult to be compatible with PBAT. At the same time, hydrogen bonds are easily formed between starch hydroxyl groups. The strong intermolecular hydrogen bonding force makes the viscosity flow temperature of starch higher than its decomposition temperature, and it is not thermoplastic and has poor processability. Therefore, thermal processing and high performance of starch through modification are important means to expand the application range of starch materials.
[0003] At present, the main ways to modify starch are physical modification and chemical modification. In the process of physical modification of starch, sorbitol, ethylene glycol, etc. are used as plasticizers to prepare thermoplastic starch, thereby improving the compatibility of starch with PBAT. Chemical modification mainly uses chemical reactions to react with hydroxyl groups in starch using modifiers. For example, citric acid, adipic acid, malic acid, etc. are used as cross-linking agents to cross-link starch through esterification reactions to improve the mechanical and processing properties of starch. For another example, tartaric acid is used to acidify starch to improve the hydrophobicity of starch. The above examples have the problem that small molecule plasticizers are easy to migrate and the plasticization efficiency is low; or the process conditions of the reaction between the cross-linking agent and starch are complex and the degree of cross-linking is low; or the acidification process of the acidifier on starch will cause the molecular weight to decrease and the viscosity to decrease. The plasticity of the modified starch obtained by the above method has not been greatly improved, and there is still a problem of compatibility between PBAT and starch, and the mechanical and thermal properties of the composite material have not been significantly improved. Summary of the invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a modified starch based on graft copolymerization, a preparation method and an application in PBAT. The modified starch of the present invention has high strength and high toughness, and after being blended with PBAT, the processing performance, mechanical properties and thermal properties of the composite material are significantly improved.
[0005] The preparation method of modified starch based on graft copolymerization proposed by the present invention comprises the following steps:
[0006] S1: gelatinization of starch;
[0007] S2: adding the gelatinized starch of S1 to a premixed solution of crotonyl chloride, triaminobenzyl alcohol and triethylamine, and then adding an initiator to react, and after the reaction, precipitating, washing and drying to obtain a grafted starch;
[0008] S3: S2 grafted starch is blended with a composite plasticizer, and after uniform mixing, the mixture is melt-extruded to obtain modified starch.
[0009] Preferably, the gelatinization temperature of the starch in S1 is 80-100°C and the time is 20-40 min.
[0010] Preferably, the mass ratio of gelatinized starch, crotonyl chloride, triaminobenzyl alcohol and triethylamine in S2 is 20-60:0.5-2:0.2-1.2:0.5-2.
[0011] Preferably, the reaction temperature in S2 is 30-80°C and the reaction time is 2-8h.
[0012] Preferably, the composite plasticizer in S3 is composed of urea and glycerol in a mass ratio of 2-4:1.
[0013] Preferably, the mass ratio of grafted starch to composite plasticizer in S3 is 100:20-40; the conditions for melt extrusion are: screw speed is 100-300r / min, feeding speed is set to 3-5r / min, and extrusion temperature zone is set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 150, 145°C.
[0014] The modified starch based on graft copolymerization is prepared by the above method proposed in the present invention.
[0015] The present invention proposes the application of the modified starch based on graft copolymerization in PBAT.
[0016] Preferably, the method comprises the following steps: PBAT and modified starch are mixed at high speed and then melt-extruded.
[0017] Preferably, the mass ratio of PBAT to modified starch is 100:10-40; the high-speed mixing temperature is 30-45°C, and the time is 10-30min; the conditions for melt extrusion are: the screw speed is 200-400r / min, the feeding rate is 5-7r / min, and the extrusion temperature zone is set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150°C.
[0018] Beneficial technical effects of the present invention:
[0019] The present invention proposes to use crotonyl chloride and triaminobenzyl alcohol as monomers to graft with starch to construct a ternary system, and introduces amide and ester functional groups on the starch surface to reduce the hydrogen bonding between starch molecules and within the molecules, thereby improving plasticity and processability.
[0020] The present invention establishes a dual preparation process of "grafting-plasticization", and the obtained modified starch has high strength, high toughness and good compatibility with PBAT, and significantly improves the mechanical properties and thermal properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Infrared spectra of the St, CCAA-1, St-g-CCAA-1, and TP-St-g-CCAA-1 samples proposed in the present invention;
[0022] Figure 2 The crystallization / melting curve comparison diagram of PBAT, PBAT / St-1 and PBAT / TP-St-g-CCAA-1 proposed in the present invention; wherein (a) is the crystallization process of cooling, and (b) is the melting process of heating;
[0023] Figure 3 Schematic diagram of the synthesis mechanism of St-g-CCAA proposed in the present invention;
[0024] Figure 4 This is a schematic diagram of the hydrogen bonding mechanism of the composite plasticizer proposed in the present invention. DETAILED DESCRIPTION
[0025] The present invention will be further explained below in conjunction with specific embodiments.
[0026] The starch of the present invention can be plant starch, specifically corn starch, sweet potato starch and cassava starch, etc. In the specific implementation, corn starch is selected, the mesh size is 100 mesh, the moisture content is 9.69%, and the whiteness is 89.9%; the initiator of the present invention can be a persulfate such as potassium persulfate or ammonium persulfate, or an existing well-known initiator that can be used for starch grafting reaction. In the specific implementation, potassium sulfate is used as an initiator for testing; the PBAT selected in the specific implementation of the present invention has a melt index (190°C, 2160g) of 3.42g / 10min, a melting point of 118.49°C, and a carboxyl content of 13.27mol / t.
[0027] Example 1
[0028] Weigh 500g corn starch (St) and add it to 1670g deionized water, stir and seal in N 2atmosphere; then, heated at 95°C for 30 min to obtain gelatinized starch.
[0029] 9.3 g of triaminobenzyl alcohol (AA) was weighed and added to 200 mL of chloroform to form a solution, and 15.6 g of crotonyl chloride (CC) was slowly dropped into the above solution to obtain a mixed solution; then, the temperature was raised to 38° C., and 13.2 g of triethylamine (TEA) was dropped into the above mixed solution to obtain a solution recorded as CCAA-1 solution.
[0030] The CCAA-1 solution was added to the gelatinized starch, the temperature was raised to 50°C, and 5 g of potassium persulfate (KPS) was added, and the reaction was stirred for 4 hours. After the reaction was completed, 120 mL of methanol was added, and the mixture was extracted at 80°C to obtain a precipitate. Then, the precipitate was washed and dried in an oven at 80°C for 8 hours to obtain grafted starch, which was recorded as St-g-CCAA-1.
[0031] Weigh 45g of glycerol and 135g of urea into a beaker and mix evenly; then, place the mixed composite plasticizer and 450g of St-g-CCAA-1 in a high-speed mixer and mix at a speed of 600r / min for 20min; then, melt-extrude the mixed raw materials, the screw speed is 200r / min, the feeding rate is set to 4r / min, the extrusion temperature zone is set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 155, 150, 145°C, and the obtained product is recorded as TP-St-g-CCAA-1.
[0032] Weigh 200g TP-St-g-CCAA-1 and 1kg PBAT into a high-speed mixer and mix at a speed of 500r / min for 20min; then, melt-extrude the uniformly mixed raw materials, the screw speed is 200r / min, the feeding speed is set to 6r / min, and the extrusion temperature zone is set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150°C to obtain a composite material recorded as PBAT / TP-St-g-CCAA-1.
[0033] Example 2
[0034] Weigh 500g St and add it to 1670g deionized water, stir and seal in N 2 atmosphere; then, heated at 95°C for 30 min to obtain gelatinized starch.
[0035] 9.8 g of AA was weighed and added to 200 mL of chloroform to form a solution, and 16.4 g of CC was slowly dropped into the above solution to obtain a mixed solution; then, the temperature was raised to 38° C., and 13.2 g of TEA was dropped into the above mixed solution to obtain a solution recorded as CCAA-2 solution.
[0036] The CCAA-2 solution was added to the gelatinized starch, the temperature was raised to 50°C, and 5 g of potassium persulfate was added, and the reaction was stirred for 4 hours. After the reaction was completed, 120 mL of methanol was added, and the mixture was extracted at 80°C to obtain a precipitate. Then, the precipitate was washed and dried in an oven at 80°C for 8 hours to obtain grafted starch, which was recorded as St-g-CCAA-2.
[0037] Weigh 45g of glycerol and 135g of urea into a beaker and mix evenly; then, place the mixed composite plasticizer and 450g of St-g-CCAA-2 in a high-speed mixer and mix at a speed of 600r / min for 20min; then, melt-extrude the mixed raw materials, the screw speed is 200r / min, the feeding rate is set to 4r / min, the extrusion temperature zone is set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 150, 145°C, and the product is recorded as TP-St-g-CCAA-2.
[0038] Weigh 200g TP-St-g-CCAA-2 and 1kg PBAT into a high-speed mixer and mix at a speed of 500r / min for 20min; then, melt-extrude the uniformly mixed raw materials, the screw speed is 200r / min, the feeding speed is set to 6r / min, and the extrusion temperature zone is set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150°C to obtain a composite material recorded as PBAT / TP-St-g-CCAA-2.
[0039] Example 3
[0040] Weigh 500g St and add it to 1670g deionized water, stir and seal in N 2 atmosphere; then, heated at 95°C for 30 min to obtain gelatinized starch.
[0041] 8.8 g of AA was weighed and added to 200 mL of chloroform to form a solution, and 14.9 g of CC was slowly dropped into the above solution to obtain a mixed solution; then, the temperature was raised to 38° C., and 13.2 g of TEA was dropped into the above mixed solution to obtain a solution recorded as CCAA-3 solution.
[0042] The CCAA-3 solution was added to the gelatinized starch, the temperature was raised to 50°C, and 5 g of potassium persulfate was added. The reaction was stirred for 4 h. After the reaction was completed, 120 mL of methanol was added and extracted at 80°C to obtain a precipitate. Then, the precipitate was washed and dried in an oven at 80°C for 8 h to obtain grafted starch, which was recorded as St-g-CCAA-3.
[0043] Weigh 45g of glycerol and 135g of urea into a beaker and mix evenly; then, place the mixed composite plasticizer and 450g of St-g-CCAA-3 in a high-speed mixer and mix at a speed of 600r / min for 20min; then, melt-extrude the mixed raw materials, the screw speed is 200r / min, the feeding rate is set to 4r / min, the extrusion temperature zone is set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 150, 145°C, and the product is recorded as TP-St-g-CCAA-3.
[0044] 200 g TP-St-g-CCAA-3 and 1 kg PBAT were weighed and placed in a high-speed mixer and mixed at a speed of 500 r / min for 20 min; then, the uniformly mixed raw materials were melt-extruded, the screw speed was 200 r / min, the feeding speed was set to 6 r / min, and the extrusion temperature zone was set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150 ° C to obtain a composite material recorded as PBAT / TP-St-g-CCAA-3.
[0045] Comparative Example 1
[0046] Weigh 200g St and 1kg PBAT, place them in a high-speed mixer, and mix them at a speed of 500r / min for 20min; then, melt and extrude the uniformly mixed raw materials, the screw speed is 200r / min, the feeding speed is set to 6r / min, the extrusion temperature zone is set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150°C, and the obtained composite material is recorded as PBAT / St-1.
[0047] Comparative Example 2
[0048] Weigh 135g of urea and 45g of glycerol into a beaker and mix them evenly; then, place the mixed composite plasticizer and 450g of St in a high-speed mixer and mix them at a speed of 600r / min for 20min. After mixing, melt extrude the mixture, the screw speed is 200r / min, the feeding speed is set to 4r / min, the extrusion temperature zone is set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 150, 145°C, and the product is recorded as TPSt-1.
[0049] Weigh 200g TPSt-1 and 1kg PBAT, place them in a high-speed mixer, and mix them at a speed of 500r / min for 20min; then, melt and extrude the uniformly mixed raw materials, the screw speed is 200r / min, the feeding speed is set to 6r / min, and the extrusion temperature zone is set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150°C to obtain a composite material recorded as PBAT / TPSt-1.
[0050] Comparative Example 3
[0051] Weigh 180g of urea and place it in a beaker; then, place the plasticizer and 450g of St-g-CCAA-1 in a high-speed mixer and mix at a speed of 600r / min for 20min; then, melt-extrude the mixed raw materials, the screw speed is 200r / min, the feeding rate is set to 4r / min, the extrusion temperature zone is set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 150, 145°C, and the product is recorded as TP-St-g-CCAA-4.
[0052] 200 g TP-St-g-CCAA-4 and 1 kg PBAT were weighed and placed in a high-speed mixer and mixed at a speed of 500 r / min for 20 min; then, the uniformly mixed raw materials were melt-extruded, the screw speed was 200 r / min, the feeding speed was set to 6 r / min, and the extrusion temperature zone was set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150 ° C to obtain a composite material recorded as PBAT / TP-St-g-CCAA-4.
[0053] Comparative Example 4
[0054] Weigh 180g of glycerol and place it in a beaker; then, place the plasticizer and 450g of St-g-CCAA-1 in a high-speed mixer and mix at a speed of 600r / min for 20min; then, melt-extrude the mixed raw materials, the screw speed is 200r / min, the feeding rate is set to 4r / min, the extrusion temperature zone is set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 150, 145°C, and the product is recorded as TP-St-g-CCAA-5.
[0055] Weigh 200g TP-St-g-CCAA-5 and 1kg PBAT into a high-speed mixer and mix at a speed of 500r / min for 20min; then, melt-extrude the uniformly mixed raw materials, the screw speed is 200r / min, the feeding speed is set to 6r / min, and the extrusion temperature zone is set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, 150°C to obtain a composite material recorded as PBAT / TP-St-g-CCAA-5.
[0056] The present invention conducts mechanical property tests on the samples prepared in Examples 1-3 and Comparative Examples 1-4, and the results are shown in Table 1. The standards for the flexural strength and flexural modulus tests are GB / T9341-2008 "Plastics - Determination of Flexural Properties"; the standards for the tensile strength and elongation at break tests are GB / T1040.1-2018 "Plastics - Determination of Tensile Properties".
[0057] Table 1 Mechanical properties of samples
[0058]
[0059] As can be seen from Table 1, the sample PBAT / TP-St-g-CCAA-1 prepared in Example 1 has the best mechanical properties, with a tensile strength of 25.43MPa, an elongation at break of 670%, and a flexural strength of 4.78MPa. Compared with pure PBAT, the tensile strength of the composite material decreased by 22.6%, the elongation at break increased by 15.5%, and the flexural strength increased by 47.07%. Overall, the mechanical properties of PBAT / TPSt-1 are better than those of the PBAT / St-1 sample, and the plasticization efficiency of the starch modified by graft copolymerization is higher, and the mechanical properties after blending with PBAT are higher than those of the PBAT / TPSt-1 sample. Compared with the PBAT / TPSt-1 sample, the tensile strength of PBAT / TP-St-g-CCAA-1 increased by 38.6%, the elongation at break increased by 17.5%, and the flexural strength increased by 53.2%. It can also be seen from Example 1, Comparative Examples 3 and 4 that the use of a compound plasticizer can improve the plasticization efficiency of starch, thereby further enhancing the mechanical properties of the composite material.
[0060] The present invention performs infrared detection and analysis on CCAA-1, St, St-g-CCAA-1 and TP-St-g-CCAA-1 samples in Example 1, and the results are as follows: Figure 1 As shown. Figure 1 It can be obtained at 1000cm -1 The peaks at 1720 cm-1 are the COC stretching vibration peaks of the glycosidic bond of St, St-g-CCAA-1 and TP-St-g-CCAA-1. -1 The C=O peak appears, but this vibration is not found in St, which indicates that CCAA-1 has been grafted onto the main chain of St. The center position of the St hydroxyl peak is 3200-3400cm -1 The absorption peak is relatively broad, which is due to the large number of free hydroxyl groups in the starch molecular chain. However, after graft copolymerization, the peak areas of the hydroxyl characteristic peaks of St-g-CCAA-1 and TP-St-g-CCAA-1 were reduced, indicating that the hydroxyl groups in the starch reacted with the active groups in the grafted monomers, reducing the hydroxyl content in the starch. In addition, by adding glycerol and urea composite plasticizers, the hydrogen bonds between starch molecules were destroyed, and the hydroxyl peak vibration shifted to a high wave number, from 3300 cm -1 Blue shift to 3320cm -1 .
[0061] The present invention performs differential thermal scanning tests on PBAT samples, PBAT / St-1 and PBAT / TP-St-g-CCAA-1. The results are as follows: Figure 2 The details of the thermodynamic parameters of the samples are shown in Table 2.
[0062] Table 2 Thermodynamic parameters of samples
[0063]
[0064] Depend on Figure 2As can be seen from Table 2, pure PBAT shows an obvious exothermic peak curve, and a strong melting crystallization peak is observed at 37.62°C. With the addition of St and TP-St-g-CCAA-1, the melting and crystallization temperature of PBAT increases, indicating that the addition of St and TP-St-g-CCAA-1 promotes the crystallization of PBAT. The crystallization temperature of PBAT / TP-St-g-CCAA-1 reaches 47.22°C, and the crystallization effect is the best. This is because the amorphous phase of TP-St-g-CCAA-1 activates the fluidity of the PBAT chain, making it easier for the chain to move and arrange regularly. In addition, PBAT has a glass transition at around -32.80°C, followed by a melting peak at 121.81°C. After adding St and TP-St-g-CCAA-1, the T of PBAT g Moving towards low temperature, T m Move towards high temperature. g The decrease indicates that TP-St-g-CCAA-1 reduces the molecular chain movement of PBAT, and PBAT has a high compatibility with TP-St-g-CCAA-1; T m The increase indicates that the interaction between TP-St-CCAA-1 molecules and PBAT molecular chains is stronger, and the heat resistance is improved.
[0065] It can also be seen from the thermodynamic parameters in Table 2 that PBAT / TP-St-g-CCAA-1 has higher , and PBAT / TP-St-g-CCAA-1 has a higher crystallinity. This is because the TP-St-g-CCAA-1 modified by graft copolymerization increases the molecular chain length and improves the interaction with PBAT; TP-St-g-CCAA-1 has stronger plasticity and better molecular chain fluidity, which promotes the regular arrangement of molecular chain movement.
[0066] Figure 3 Schematic diagram of the synthesis mechanism of St-g-CCAA proposed in the present invention; Figure 4 Schematic diagram of the hydrogen bonding mechanism of the composite plasticizer proposed in the present invention. Figure 3 As shown, the present invention utilizes AA and CC to react chemically under the catalytic action of TEA to obtain a grafted monomer CCAA; the hydroxyl groups on the starch surface and the double bonds of CCAA undergo graft copolymerization under the action of potassium persulfate to obtain St-g-CCAA. This reaction reduces the content of hydrophilic hydroxyl groups and enhances the hydrophobicity of starch, thereby improving its application in non-polar or hydrophobic matrices. Figure 1 From the above, it can be seen that the characteristic peak area of St hydroxyl groups is reduced after graft copolymerization modification, which changes the surface properties of the St matrix and thus improves its compatibility with PBAT.
[0067] like Figure 4As shown, the present invention modifies starch by adding glycerol and urea composite plasticizers. Urea, as an amide plasticizer, enters the molecules through penetration, and its amide group destroys the hydrogen bonds between the original starch molecules while forming more stable hydrogen bonds with the starch hydroxyl groups, increasing the distance between the starch molecules, thereby reducing the intermolecular forces, and achieving the purpose of plasticizing starch to prepare thermoplastic starch. Glycerol has a small relative molecular weight and contains more hydroxyl groups. When plasticizing starch, it can be interspersed in different starch molecules, combine with the hydroxyl groups in the starch molecules to form hydrogen bonds, reduce the hydrogen bonding between the starch molecules, thereby improving the plasticizing effect, and further plasticizing starch. According to the mechanical properties in Table 1, PBAT / TPSt-1 has greater mechanical strength than PBAT / St-1 composite materials, with tensile strength increased from 14.23MPa to 18.35MPa, and flexural strength increased from 2.35MPa to 3.12MPa.
Claims
1. A method for preparing modified starch based on graft copolymerization, characterized in that: The steps are as follows: S1: gelatinization of starch; S2: adding the gelatinized starch in S1 to a premixed solution of crotonyl chloride, 3-aminobenzyl alcohol and triethylamine, and then adding an initiator to react, and after the reaction, precipitating, washing and drying to obtain grafted starch; S3: blending the S2 grafted starch with the composite plasticizer, and then melt-extruding after mixing evenly to obtain modified starch; The mass ratio of gelatinized starch, crotonyl chloride, 3-aminobenzyl alcohol and triethylamine in S2 is 20-60:0.5-2:0.2-1.2:0.5-2; The composite plasticizer in S3 is composed of urea and glycerol in a mass ratio of 2-4:1; The mass ratio of grafted starch to composite plasticizer in S3 is 100:20-40.
2. The method for preparing modified starch based on graft copolymerization according to claim 1, characterized in that: The gelatinization temperature of the starch in S1 is 80-100°C and the time is 20-40 minutes.
3. The method for preparing modified starch based on graft copolymerization according to claim 1, characterized in that: The reaction temperature in S2 is 30-80°C and the reaction time is 2-8h.
4. The method for preparing modified starch based on graft copolymerization according to claim 1, characterized in that: The conditions for melt extrusion are: screw speed is 100-300 r / min, the feeding rate is set to 3-5 r / min, and the extrusion temperature zones are set to 125, 130, 135, 140, 145, 150, 155, 155, 155, 150, 145°C.
5. Modified starch based on graft copolymerization prepared by the method according to any one of claims 1 to 4.
6. Use of the modified starch based on graft copolymerization as claimed in claim 5 in PBAT.
7. The use of modified starch based on graft copolymerization in PBAT according to claim 6, characterized in that: The method comprises the following steps: PBAT and modified starch are mixed at high speed and then melt-extruded.
8. The use of modified starch based on graft copolymerization in PBAT according to claim 7, characterized in that: The mass ratio of PBAT and modified starch is 100:10-40; the high-speed mixing temperature is 30-45°C, and the time is 10-30min; the conditions for melt extrusion are: the screw speed is 200-400r / min, the feeding rate is 5-7r / min, and the extrusion temperature zones are set to 130, 135, 140, 145, 150, 155, 160, 160, 160, 160, 155, and 150°C.
Citation Information
Patent Citations
Degradable starch-based plastic
CN102690488A
Modified starch, preparation method thereof and degradable plastic
CN116217811A